Laboratory Analysis of Antiphospholipid Antibodies with Clinical Correlation: A Hospital-Based 10 Year Study. (28th October 2021) - Myrzykowski, M; Xie, C; Sweet, R; Xie, M
Abstract: Introduction/Objective: Antiphospholipid syndrome (APS) is an autoimmune disorder and its diagnosis requires both laboratory evaluation of antiphospholipid antibodies (APAs) and clinical correlation. This study focused on the laboratory analysis of APS with clinical correlation in a hospital-based patient population. Methods/Case Report: From 2010-2020, immunological studies for APAs were performed at Department of Pathology, William Beaumont Hospital – Troy, Michigan and patients with positive results were selected for further analysis. Four APAs were included: IgG and IgM beta-2 glycoprotein I antibodies (IgG B2GA and IgM B2GA), and IgG and IgM anticardiolipin antibodies (IgG ACA and IgM ACA). Clinical information was collected from hospital electronic medical chart with focus on thromboembolism and abortion history, autoimmune disorders, antithrombotic therapies and other studies. Results (if a Case Study enter NA): There were 167 patients, 136 females and 31 males (F/M=4.4). The median age for females was 50 and for males, 57. Overall, B2GA was present more than ACA (102/81) in females, and ACA was present slightly more than B2GA (20/17) in males. IgM APAs were much more common than IgG APAs; IgM B2GA/IgG B2GA: 87/32 (p<0.01) and IgM ACA/IgG ACA: 81/20 (p<0.01). Most APAs were at the low-intermediate titer range and increased APAs titer correlated with decreased positive rate: APAs titer at 20-40, 41-80 and >80 with positive results at 115, 61 and 44 respectively. In addition to documented autoimmune disorders, pregnancy miscarriage was a common clinical condition (24/66) in females at age <45. But for females at age >45, vascular thrombosis became more common (18/70). Vascular thrombosis was a common clinical disease in males (16/31) followed by autoimmune disorders (10/31). Most patients with vascular thrombosis received antithrombotic therapies. Conclusion: Female patients positive for APAs was significantly more and younger than males in this study. IgM B2GA was the most common type of APAs followed by IgM ACA. IgG B2GA and IgG ACA were much less common. In younger female patients autoimmune disorders and abortion were the most common clinical conditions. In older female and male patients, autoimmune disorders and vascular thrombosis were the most common clinical conditions. The titer of APAs detected was at low-intermediate range in most patients. The relationship between the titer of APAs and clinical conditions needs further study.